The Commercialisation of Accountancy: Flexible Accumulation and the Transformation of the Service Class. - Ketz, J. Edward; Boatsman, James R. (The Accounting Review, 1996)
Reviews the book `The Commercialisation of Accountancy: Flexible Accumulation and the Transformation of the Service Class,' by Gerard Hanlon.